Project-based learning management in strengthening students’ collaboration and communication skills in elementary school - Nafa Rupita; Manap Somantri; Muhammad Kristiawan (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study aimed to describe how project-based learning management supports the development of students’ collaboration and communication skills at SD Negeri 5 Muara Rupit. A descriptive qualitative approach was employed to examine classroom interaction, teacher facilitation, and students’ learning experiences during project-based learning activities. The participants were selected through purposive sampling and consisted of one school principal, three upper-grade classroom teachers, and six students who represented active, moderate, and less active participation in group work. Data were collected through classroom observations, semi-structured interviews, and documentation analysis, including teaching modules, lesson plans, project worksheets, students’ project products, classroom photographs, and school records. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, conclusion drawing, and verification. Trustworthiness was strengthened through source triangulation, technique triangulation, repeated observations, member checking, and detailed field notes. The findings showed that project-based learning was managed through instructional planning, structured group organization, task distribution, teacher guidance, classroom interaction control, and reflective evaluation. Collaboration skills were supported through task sharing, teamwork, peer assistance, and collective problem-solving, while communication skills were supported through group discussions, idea expression, active listening, peer responses, and project presentations. The findings also revealed that teacher facilitation was essential in encouraging passive students and maintaining balanced group interaction. However, unequal participation, low confidence, limited time, limited facilities, and group management challenges remained obstacles. This study suggests that project-based learning can support collaboration and communication skills when it is managed systematically and contextually.